BIOLUBRICANT BASE STOCK SYNTHESIS FROM NON-TRADITIONAL (MAHUA) OIL USING MODIFIED GLYCEROL - DR. V.Y. KARADBHAJNE; PROF. A.J. AGRAWAL; DR. P.S. AGRAWAL; MEHERESH GUPTA (International Journal of Innovations in Engineering Research and Technology, 2021)
With the increasing demand of mineral-oil based lubricants, they are burdened by environmental issues and depleting supplies. Constantly efforts are made by the technologists to reduce the use of fossil fuels for sustainable development. Due to this, the renewable sources of lubricants have gained significant importance in this environmental-concerned world. India is endowed with over 100 species of non-traditional oils that have not been focused for the commercial applications till the date. Though these oils are in abundance, their potential has not been utilized. Such oils with the high oleic acid content are considered to be the best alternative source to substitute the mineral oil based lubricating oils. In this paper mahua oil was selected as a raw material to produce biolubricant. It was initiallytransesterified to yield mahua methyl esters and further converted to biolubricant using trimethylolpropane (TMP). The biolubricant thus prepared was analyzed for its properties and was compared with a commercial 2T Engine oil. This chemically modified ester is relevant for performance as a lubricant in various industrial applications. In addition to this, an alternative to TMP in the form of modified glycerol was found and the properties of the biolubricants produced using TMP and modified glycerol were compared.